Validation and Psychometric Evaluation of the Physical Activity Enjoyment Scale in a Bilingual-Speaking Indian College Students Population (International Journal of Food and Nutritional Sciences, 2022)
The Physical Activity Enjoyment Scale (PACES) is a widely recognized instrument for assessing an individual's enjoyment of physical activity. This study aimed to validate and assess the psychometric properties of the PACES-18 in a population of Indian college female students. The research also seeks to address the scarcity of Indian-specific descriptions of the scale, considering the multilingual and diverse nature of the country. Data from 300 college female students were collected to adapt the PACES-18 into the Indian context, emphasizing its potential utility in bilingual-speaking populations. The study discusses the relevance of cross-cultural research to understand the general applicability of the PACES-18 in diverse cultural contexts.